ANALISIS KESEIMBANGAN HUKUM ANTARA HAK GURU (PASAL 14 UNDANG-UNDANG GURU DAN DOSEN) DENGAN HAK ANAK (PASAL 54 UNDANG-UNDANG PERLINDUNGAN ANAK) MELALUI PENDEKATAN DISIPLIN POSITIF DI SMPN 2 KAUMAN TULUNGAGUNG - Hendra Abdul Rokhim; Mohammad Hasib; Bachrul Ulum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the legal balance between teacher rights, as stipulated in Article 14 of Law No. 14 of 2005 on Teachers and Lecturers, and child rights, particularly the protection from violence under Article 54 of Law No. 35 of 2014 on Child Protection, within the context of SMPN 2 Kauman Tulungagung. The research employs a qualitative methodology with an intrinsic case study design, focusing on how the school manages the tension between these two legal frameworks through a positive discipline approach. The findings indicate that SMPN 2 Kauman Tulungagung has successfully formulated policies that bridge these often-conflicting legal interests. The policy-making process is participatory, involving school committees, teachers, and supervisors. These policies are formalized through a School Head's Decree on the Standard Operational Procedure for Child-Friendly Discipline Enforcement, which includes transparent student regulations. This ensures that teachers' rights to enforce discipline are recognized, but the methods used are entirely free from physical or psychological violence, aligning with Article 54Over the past four years, the school has reported no legal complaints against teachers from parents, fostering a sense of security for educators and high trust from parents. Interestingly, parental complaints about excessive academic workload became a catalyst for the school to re-evaluate student learning burdens. The positive discipline model, implemented through preventive measures like character-building routines (e.g., 5S culture) and corrective actions such as logical consequences (e.g., cleaning the school, caring for plants, writing reflective essays), has led to increased self-awareness and a sense of belonging among students. While the transition to positive discipline is ongoing, with minor physical sanctions still occasionally occurring, the school demonstrates a commitment to continuous dialogue and improvement to maintain a balanced and child-friendly educational environment